2023
DOI: 10.1128/spectrum.02180-23
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia interferes with Zika virus replication by hijacking cholesterol metabolism in mosquito cells

Brent Edwards,
Elodie Ghedin,
Denis Voronin

Abstract: Zika virus is a member of the arbovirus Flaviviridae family transmitted by Aedes mosquitos and it is associated with microcephaly in infants born to infected mothers. Wolbachia is an intracellular gram-negative alpha-proteobacteria that infects many species of arthropods, including mosquitos. The presence of Wolbachia in mosquitos has been shown to control the vector population and suppress arbovirus transmission. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…These results suggest that w Au could show unique features in its inhibition of arboviruses compared to previously characterized Wolbachia strains. Further, Wolbachia was shown to interfere with Zika virus replication by hijacking cholesterol metabolism in mosquito cells [ 136 ].…”
Section: Pillar I—community Participationmentioning
confidence: 99%
“…These results suggest that w Au could show unique features in its inhibition of arboviruses compared to previously characterized Wolbachia strains. Further, Wolbachia was shown to interfere with Zika virus replication by hijacking cholesterol metabolism in mosquito cells [ 136 ].…”
Section: Pillar I—community Participationmentioning
confidence: 99%
“…Perturbations in such pathways have been shown to be involved in Wolbachia -mediated antiviral activity against flaviviruses. The ability of the strains w Mel and w MelPop to block flaviviruses DENV and ZIKV in both Aedes aegypti and Aedes albopictus is at least partially due to changes in cholesterol dynamics and lipid metabolism [ 12 , 13 , 14 ]. It has been shown that strain w Au does not cause similar perturbations in Aedes cells/mosquitoes, and it is likely that they do not play an important role in the ability of w Au to block arbovirus replication [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the gut bacterium Serratia marcescens facilitates DENV and ZIKV infection by secreting a bacterial effector that degrades glycosylated membrane-bound mucins on mosquito gut epithelia ( 13 ). Wolbachia , an endosymbiotic microorganism, also interrupts viral replication, possibly through the modulation of mosquito immune or physiological responses ( 14 , 15 ). Recent studies have demonstrated a substantial decrease in dengue transmission in areas where Wolbachia -infected mosquitoes were released as compared with that found in control areas ( 16 ).…”
mentioning
confidence: 99%